Frequency-Diverse Holographic Metasurface Antenna for Near-Field Microwave Computational Imaging - Han, Jiaqi; Li, Long; Tian, Shuncheng; Ma, Xiangjin; Feng, Qiang; Liu, Haixia; Zhao, Yu; Liao, Guisheng (Frontiers in Materials, 2021)
This paper presents a holographic metasurface antenna with stochastically distributed surface impedance, which produces randomly frequency-diverse radiation patterns. Low mutual coherence electric field patterns generated by the holographic metasurface antenna can cover the K-band from 18 GHz to 26 GHz with 0.1 GHz intervals. By utilizing the frequency-diverse holographic metasurface (FDHM) antenna, we build a near-field microwave computational imaging system based on reflected signals in the frequency domain. A standard horn antenna is adopted to acquire frequency domain signals radiated from the proposed FDHM antenna. Detail imaging restoration process is presented and desired targets are correctly reconstructed using the 81 frequency-diverse patterns through full-wave simulation studies. Compressed sensing technique and iterative shrinkage/thresholding algorithms are applied for the imaging reconstruction. The achieved compressive ratio of this computational imaging system on the physical layer is 30:1.